Training on Developing Children's Social Character Through Sundanese Cultural Values - Eldi Mulyana Mulyana; Ade Suherman; Triani Widyanti; Tetep Tetep; Asep Supriyatna; Fadlika Sulaeman; Hilmi Hilmi; Nurdin Miptahul Ulum; Irwan Nurkholis; Nia Kurniawan (Fakultas Kewirausahaan Universitas Garut, 2020)
The purpose of this service is to provide counseling and training for residents in Sukamanah Village, Cigalontang District, Tasikmalaya Regency, West Java Province, to develop children’s social character through Sundanese cultural values. The method used is to give lectures related to the theory and continued with parenting training through Sundanese cultural values. The results of the evaluation of this activity can be concluded that there is an increase in knowledge, attitudes and skills about parenting through the value of Sundanese culture to develop the social character of children. All community members in the area are very enthusiastic and understand about methods to develop children’s social character through Sundanese cultural values after undergoing counseling and training. Counseling and training is carried out well because the majority of people in the place are Sundanese so they can easily apply what they have been trained.